MECHANISMS FOR INCREASING LEGAL LITERACY THROUGH THE CONTINUING EDUCATION SYSTEM (ON THE EXAMPLE OF THE PRE-SCHOOL EDUCATION SYSTEM) - Panferova Irina Vitalievna; Komilova Muslima (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
The article discusses the scientific and theoretical foundations of improving legal literacy in the continuing education system and the mechanisms for effectively implementing this process in preschool educational organizations. The importance of the cooperation of teachers, parents and the public in the formation of legal awareness and culture in students is also analyzed.